INQUIRY OF A MUSIC (UN)EDUCATION - Eduardo Guedes Pacheco (Editora da Universidade de Santa Cruz do Sul, 2014)
This inquiry is an object of PhD thesis named By a Music (Un) Education carried out in the Education Graduate Program of Federal University of Rio Grande do Sul in December 2011. On the other hand, this work also make the Education Observatory Escrileituras - One Way to Read and Write in the Midst of Life, a project approved at 038/2010 public notice - MEC Education Observatory joined to CAPES and INEP with general coordination executed by Prof. Dr.ª Sandra Mara Corazza. The essay has un as prefix for act of creation and it makes available to intertwined propositions with Music Education having the Philosophy of Difference as intercessor and driving of compositional process associated to Music and Music Education.